2018
DOI: 10.1590/s1413-41522018167115
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento e modelagem da qualidade de água em uma bacia hidrográfica semiárida

Abstract: RESUMO O artigo teve como objetivo apresentar uma metodologia para caracterização da qualidade de água na Bacia Hidrográfica do Açude Acarape do Meio, no semiárido brasileiro. O mapeamento do uso do solo e o monitoramento de parâmetros de qualidade de água possibilitaram a identificação de fontes poluidoras e a construção do diagnóstico da bacia. A partir da modelagem da qualidade de água, 37 km do Rio Pacoti foram classificados como classe 4, exceto sua nascente, que ficou na classe 2. As principais fontes po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
1
6
0
5
Order By: Relevance
“…The concentration permanence curve represents the frequency that its values are not exceeded (Cunha et al, 2011). This study sought to analyse the water quality from pollutant concentrations, differing from other studies that analyse the quality of the resulting loads in the water courses (Lima et al, 2018;Fantin et al, 2017;Salla et al, 2013;Teodoro et al, 2013). This analysis is more complete by virtue of assigning the simultaneous flow to each analysed moment, bringing more reality to the presented results.…”
Section: Concentrations Permanence Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration permanence curve represents the frequency that its values are not exceeded (Cunha et al, 2011). This study sought to analyse the water quality from pollutant concentrations, differing from other studies that analyse the quality of the resulting loads in the water courses (Lima et al, 2018;Fantin et al, 2017;Salla et al, 2013;Teodoro et al, 2013). This analysis is more complete by virtue of assigning the simultaneous flow to each analysed moment, bringing more reality to the presented results.…”
Section: Concentrations Permanence Curvesmentioning
confidence: 99%
“…Bitencourt (2018) reported that most works for framing water courses in Brazil use one-dimensional models of steady states. One-dimensional models, such as QUAL2E, QUAL2K and QUAL-UFMG, are used to generate current and future water quality scenarios for water courses (Lima et al, 2018;Fantin et al, 2017;Calmon et al, 2016;Salla et al, 2013;Teodoro et al, 2013;Silva, 2016;Noh et al, 2015;Babbar, 2014;Wu & Fan, 2017;Korf et al, 2017). However, it should be considered that different flow rates influence water quality behaviour, as demonstrated by Brites (2010), Ferreira et al (2016) and Calmon et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Note que, somente no Ceará, estima-se um número total de aproximadamente 30.000 reservatórios (CAMPOS et al, 2016). Logo, dada a importância desses mananciais para o abastecimento da população do Nordeste brasileiro, várias pesquisas têm sido conduzidas recentemente com o intuito de avaliar a dinâmica de fósforo em reservatórios (BEZERRA et al, 2014;VIDAL & CAPELO NETO, 2014;BAR-BOSA & CIRILO, 2015;ARAÚJO et al, 2016;PA-CHECO et al, 2016;LIMA et al, 2018). No entanto, estudos envolvendo modelagem do fósforo nesses reservatórios ainda são escassos (LIMA, 2016;ARAÚJO et al, 2019).…”
Section: Introductionunclassified
“…A crescente preocupação em relação aos impactos ocasionados pelo despejo de esgoto in natura e tratado em corpos hídricos (DANIEL et al, 2002;MARÇAL e SILVA, 2017;LIMA et al, 2018;BU et al, 2019), resultou em uma série de legislações ambientais, critérios, políticas e estudos das melhores condições de descarga e do local de despejo, de modo que os impactos sejam minimizados (OLIVEIRA e VON SPERLING, 2005).…”
Section: Introductionunclassified